2017
DOI: 10.1186/s13049-017-0449-y
|View full text |Cite
|
Sign up to set email alerts
|

Low sensitivity of qSOFA, SIRS criteria and sepsis definition to identify infected patients at risk of complication in the prehospital setting and at the emergency department triage

Abstract: BackgroundSepsis is defined as life-threatening organ dysfunction caused by a host response to infection. The quick SOFA (qSOFA) score has been recently proposed as a new bedside clinical score to identify patients with suspected infection at risk of complication (intensive care unit (ICU) admission, in-hospital mortality). The aim of this study was to measure the sensitivity of the qSOFA score, SIRS criteria and sepsis definitions to identify the most serious sepsis cases in the prehospital setting and at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
1
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 26 publications
6
89
1
6
Order By: Relevance
“…However, some recent studies demonstrated contrary results concerning the usefulness of the qSOFA score in patients with trauma, burns, pneumonia, leukaemia, liver cirrhosis and sepsis qSOFA, quick Sequential Organ Failure Assessment; DqSOFA, subtracting the worst value of the qSOFA score from 1 hr after presentation from the qSOFA score at presentation. [11][12][13][14][21][22][23][24][25][26][27]. These controversies are estimated to vary according to the severity of the disease, the timing of the measurement and the measurement method [22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…However, some recent studies demonstrated contrary results concerning the usefulness of the qSOFA score in patients with trauma, burns, pneumonia, leukaemia, liver cirrhosis and sepsis qSOFA, quick Sequential Organ Failure Assessment; DqSOFA, subtracting the worst value of the qSOFA score from 1 hr after presentation from the qSOFA score at presentation. [11][12][13][14][21][22][23][24][25][26][27]. These controversies are estimated to vary according to the severity of the disease, the timing of the measurement and the measurement method [22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Selanjutnya, kriteria klinis sepsis berat yaitu kriteria SIRS ditambah satu tanda disfungsi organ atau hipoperfusi yaitu Glasgow Coma Scale (GCS) <15 atau menurun dari baseline, saturasi oksigen < 90% atau tekanan darah sistolik <90 mmHg (Tabel 1). 6,10 Skor qSOFA diusulkan Sepsis 3 Task Force sebagai alat stratifikasi yang lebih spesifik daripada kriteria SIRS untuk kepentingan penilaian disfungsi organ, mengidentifikasi kondisi infeksi yang mengancam nyawa, memulai atau meningkatkan terapi sepsis secara tepat, dan merujuk pasien ke ruang rawat intensif. 3 Skor qSOFA berkisar dari 0 hingga 3, dengan satu poin diberikan untuk masing-masing tanda-tanda klinis berikut: tekanan darah sistolik ≤100 mmHg, frekuensi pernafasan ≥22 kali/mnt, dan perubahan status mental.…”
Section: Perbedaan Kriteria Sirs Dan Skor Qsofaunclassified
“…In this meta-analysis, 35 studies with 269,544 patients reported on the prognostic accuracy of the qSOFA and short-term mortality, including 27 retrospective studies [5][6][7][8]10,11,[13][14][15][16]18,20,22,[24][25][26][27]29,[32][33][34][35][37][38][39][40] , while 8 studies were prospective studies 9,12,17,19,21,23,28,30,36 . Due to the heterogeneity of the inclusion criteria, a random-effects model was used to calculate the pooled sensitivity and specificity of the included studies.…”
Section: The Qsofa and Short-term Mortalitymentioning
confidence: 99%